Exploration of factors influencing the adoption and viability of classroom-based physical activity among primary school teaching staff : A thematic synthesis of qualitative empirical research - Szergejev, Natalia (My University, 2024)
Classroom-based physical activity (PA) may provide additional opportunities for children to be active during the school day and increase their physical activity levels and motivation whilst also contributing to their positive learning experiences. However, the sustained and maintained adoption of classroom-based physical activity depends on the teaching staff. To ensure the viability of classroom-based PA as a pedagogical approach, a more comprehensive understanding of the behavioural and psychological processes that influence teaching staff’s implementation and adoption of the approach is needed. Therefore, the purpose of this study was to systematically review existing literature on teaching staff’s perspectives and beliefs towards the implementation and adoption of classroom-based PA. The aim of the study was to increase our understanding by thematically synthesising existing research on the factors that influence teaching staff’s behavioural intentions to implement and adopt classroom-based PA and thereby assessing and explaining the viability and sustainability of such methods in teaching and learning. The thematic synthesis of 13 eligible qualitative empirical studies resulted in the identification of 27 themes describing factors influencing teaching staff. The Theory of Planned Behaviour was used to explore what teaching staff’s perceptions and intentions on classroom-based PA show us about the implementation of such pedagogical approaches. The main facilitators for implementing classroom-based PA have been identified as teaching staff’s beliefs about the positive social, emotional and academic benefits of classroom-based PA for pupils, supportive school community and whole-school approach and the capability to do so. The main barriers hindering the implementation and adoption of the approaches included the evaluation of negative behavioural outcomes of physical activity in the classroom among pupils, societal and cultural expectations for teaching staff and education, as well as the lack of time for planning and delivering activities. The Theory of Planned Behaviour aligned with the main themes and could serve to explain teaching staff’s behaviour and intentions towards classroom-based physical activity. Overall, the current study acknowledged the theoretical potential of classroom-based PA, however pointed out that challenges arise in the practical implementation of the approaches. Viability and sustained use of the approach cannot be ensured without looking into and targeting teaching staff’s behaviour of implementing and adopting classroom-based physical activity approaches in teaching and learning.
Keywords: physical activity, classroom-based physical activity, teachers, theory of planned behaviour